2006
DOI: 10.1164/rccm.200508-1330oc
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Fibrosis Transmembrane Conductance Regulator Function Is Suppressed in Cigarette Smokers

Abstract: We conclude that cigarette smoke decreases the expression of CFTR gene, protein, and function in vitro and that acquired CFTR deficiency occurs in the nasal respiratory epithelium of cigarette smokers. We suggest that acquired CFTR deficiency may contribute to the physiopathology of cigarette-induced diseases such as chronic bronchitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
237
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 251 publications
(259 citation statements)
references
References 37 publications
19
237
0
3
Order By: Relevance
“…Both in vitro and in vivo studies have shown that cigarette smoke decreases the expression of cystic fibrosis transmembrane regulator (CFTR) gene, protein, and function contributing to the pathophysiology of existing CFTR deficiencies [84]. …”
Section: Resultsmentioning
confidence: 99%
“…Both in vitro and in vivo studies have shown that cigarette smoke decreases the expression of cystic fibrosis transmembrane regulator (CFTR) gene, protein, and function contributing to the pathophysiology of existing CFTR deficiencies [84]. …”
Section: Resultsmentioning
confidence: 99%
“…The recent demonstration that active smoking decreases CFTR expression at the gene and protein levels in participants without CF supports this hypothesis. 40 The observed effect of the CFTR genotype may explain why the best-powered study to date on lung function in patients with CF and secondhand smoke exposure did not detect the effect of secondhand smoke exposure on lung function in their subgroup of ΔF508 homozygotes. 4 Our findings suggest that future studies of gene-environment interactions in CF lung disease should not be solely confined to ΔF508 homozygotes because non-ΔF508 homozygotes may be better suited to detect the negative effects of modifiers of lung function.…”
Section: Commentmentioning
confidence: 99%
“…The great majority of this is in the reduced state: 96% of the GSH in ELF of nonsmokers and 98% of that in smokers are reduced. In human epithelial cells, the GSH increase induced by oxidants and cigarette smoke is associated with a simultaneous decrease in CFTR function [26,52]. CFTR function is also decreased in healthy smokers as determined by nasal potential difference measurements [52], a response that may represent an antioxidant defense aimed at transiently increasing mucus viscosity and decreasing GSH loss from epithelial cells.…”
Section: Antioxidants In the Airway Lumen Mucinmentioning
confidence: 99%